The Integrity of Islamic Politics in the Thoughts of Hasan al-Banna and Sayyid al-Qutb - Ainun Asyfia; Assyifa Rahmawati Putri; Wahyuna Wahyuna; Surya Sukti (ALSYS, 2026)
The relationship between Islam and politics has remained a central theme in modern Islamic political discourse, particularly in response to colonialism, secularism, and moral crises in Muslim societies. This study aimed to examine the integrity of Islamic political thought in the perspectives of Hasan al-Banna and Sayyid Qutb and to analyze how both thinkers conceptualized Islamic politics as an integrated system encompassing religion and state. The study employed a qualitative descriptive design with a library research approach, drawing on books, journal articles, and relevant digital sources. The findings indicate that Hasan al-Banna advanced a gradual and reformative approach through education, moral development, and organizational movements, viewing politics as an instrument for achieving social justice and public welfare based on Islamic values. By contrast, Sayyid Qutb adopted a more ideological and transformative perspective, introducing concepts such as hakimiyyah and modern jahiliyyah and advocating the comprehensive implementation of Sharia as the foundation of governance. Despite these differences in emphasis, both thinkers rejected the separation of religion and politics and maintained that Islam provides a comprehensive system regulating all aspects of life. The study concludes that the political thought of Hasan al-Banna and Sayyid Qutb makes an important contribution to contemporary Islamic political discourse by underscoring the significance of moral integrity, social reform, and the integration of religious principles in governance as foundations for justice and societal well-being.